Barriers to and facilitators of male uptake of HIV testing services in Orange Farm Township, Gauteng Province: user and provider perspectives - Chauke, Nyeleti P. (University of the Free State, 2024)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱 𝗮𝗻𝗱 𝗢𝗯𝗷𝗲𝗰𝘁𝗶𝘃𝗲𝘀: South Africa remains heavily burdened by the human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) epidemic, with devastating effects among men. Unlike women, men are increasingly unlikely to access HIV testing services (HTS) at primary health care (PHC) facilities. Male uptake of HTS is very low with high rates of HIV-related deaths among men. The 2016 South Africa Demographic and Health Survey found that although 94% of men aged 15 to 49 were aware of HIV testing locations, only 29% had undergone an HIV test. The study draws on the Socio-Ecological Model (SEM) to explore, from the perspective of both users and providers, barriers to and facilitators of men’s uptake of HTS at three PHC facilities in the Orange Farm township. The SEM illustrates how multiple factors influence an individual’s health behaviour. The SEM comprises five levels which include the individual, interpersonal, organisational, community, and policy levels. 𝗠𝗲𝘁𝗵𝗼𝗱: The researcher adopted a constructivist paradigm for this study as it is believed that individuals give meaning to their experiences through interactions with their environments. A case study design was employed, and qualitative semi-structured interviews were used as a data collection tool. The semi-structured interviews were conducted among a total of 23 conveniently selected participants including, 12 male patients, six lay counsellors and five Nurse-initiated Management of Antiretroviral Therapy (NIMART) trained professional nurses. The purpose of these sample sizes was to reach saturation as opposed to the generalisability of findings. Data were analysed thematically using the SEM constructs as a priori themes with subsequent development of subthemes. The process involved the grouping of key barriers to and facilitators of HTS perceived by male patients, lay counsellors, and professional nurses according to the SEM constructs. 𝗙𝗶𝗻𝗱𝗶𝗻𝗴𝘀:. Both users and healthcare providers perceived similar barriers to male uptake of HTS. These included, at the (1) individual level – lack of knowledge; (2) interpersonal level – negative peer and family influence; (3) organisational level – discomfort when attended by female healthcare providers; (4) community level – lack of education and awareness within the community; and (5) policy level – non-adherence to policy and privacy concerns. Again, perceived similarly by both patients and healthcare providers, facilitators of HTS included at the (1) individual-level – overcoming fear; (2) interpersonal level – fostering supportive family and friend networks; (3) organisational level – initiation of ‘male-friendly services’ in PHC facilities; (4) community level – initiating community health education and awareness tailored for men; and (5) policy level – reinforcement of policy adherence. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻𝘀: The findings indicate that barriers to and facilitators of male HTS uptake vary across the SEM levels. Both users and providers’ views highlighted a multifactorial influence on male uptake of HTS at PHC facilities, necessitating a multifaceted intervention strategy, encompassing all five SEM levels. Such efforts can result in more men accessing HIV testing at PHC facilities, enrolling in treatment, and most importantly, adopting preventative measures to curb the spread of HIV/AIDS.
Dissertation(M.Soc.Sc.(Health Systems Studies))--University of the Free State, 2024
Keywords: Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) epidemic; Primary Health Care (PHC) facilities; HIV Testing Services (HTS); 2016 South Africa Demographic and Health Survey; Socio-Ecological Model (SEM); Orange Farm township